Peran Kader Kesling sebagai Upaya Pencegahan Kejadian Dermatitis dengan Perbaikan Kualitas Air Sumur Bor - Baharuddin, Alfina; junaid, Annisa; Poetra, Ricky Perdana; Yuliati; A. Fachrin, Suharni (Bahasa Indonesia, 2024)
Abstract Clean water is one of the basic needs for human life. The results of the examination of the quality of borehole water in Moncong Loe Village obtained the level of sulfate (SO4) The level of sulfate (SO4) has exceeded the quality standard as clean water which is 400 mg / l and as drinking water is 250 mg / liter. While dermatitis cases in the area reached 65.6%.  The objectives of this service are: Improving the quality of borehole water in Pamanjengan hamlet, Maros Regency: Increase ownership of healthy water, increase understanding of water purification techniques at the household level, reduce dermatitis cases due to decreased borehole water quality. The solutions offered in this service activity are 1. Conducting knowledge transfer education related to healthy latrines according to the functions and benefits for environmental health and the practice of making septi tanks and pilot healthy latrines 2. Conducting knowledge transfer education related to water purification methods The results of the service showed that there was an increase in the knowledge of the partners from the pre-test activity in the sufficient category (83.3%) while for the post-test it increased to 88.6%. There was an increase in the attitude of the partners from the pre-test activity in the moderate category (80%) while for the post test it increased to 86.6%.There was an increase in the actions of kesling cadres from the pre-test activity in the moderate category (79.8%) while for the post test it increased to 85.6%.   Abstrak Air bersih merupakan salah satu kebutuhan pokok bagi kehidupan manusia. Hasil pemeriksaan kualitas air sumur bor di Desa Moncongloe diperoleh kadar sulfat (SO4) Kadar sulfat (SO4) tersebut telah melebihi baku mutu sebagai air bersih yaitu 400 mg/l dan sebagai air minum yaitu 250 mg/liter. Sedangkan kasus dermatitis diwilayah tersebut mencapai 65,6%. Tujuan pengabdian ini adalah: meningkatkan capaian Kualitas air sumur bor di dusun Pamanjengan Kab maros: Meningkatkan kepemilikan air yang sehat, meningkatkan pemahaman tentang teknik penjernihan air ditingkat rumah tangga, menurunkan kakuss dermatitis akibat penurunan kualitas air sumur bor. Solusi yang ditawarkan dalam kegiatan pengabdian ini adalah 1. Melakukan edukasi transfer pengetahuan terkait Jamban sehat sesuai fungsi dan manfaat bagi kesehatan lingkungan serta praktek pembuatan septi tank dam jamban sehat percontohan 2. Melakukan edukasi transfer pengetahuan terkait metode penjernihan air Hasil pengbdian menunjukkan Terjadi peningkatan pengetahuan para mitra dari kegiatan pre test kategori cukup (83,3%) sedangkan untuk post test meningkat menjadi 88,6%. Terjadi peningkatan sikap para mitra dari kegiatan pre test kategori cukup (80%) sedangkan untuk post test meningkat menjadi 86,6%.Terjadi peningkatan tindakan kader kesling dari kegiatan pre test kategori cukup (79,8%) sedangkan untuk post test meningkat menjadi 85,6% .